KAJIAN RELE JARAK DAN ARUS LEBIH PADA SADA SALURAN UDARA TEGANGAN TINGGI GARDU INDUK 150kV SRONDOL - Zalmahdi Syamsudin; Isworo Pujotomo; Fahmi Dinar Ramadhan (Sutet, 2015)
Power transmission lines play an important role in the distribution of electricity from power to consumers, therefore required effective and reliable protection equipment to maintain the continuity of the provision of electric power. The relays used on the transmission line are Release Relay, Over Current Relay (OCR) and Ground Fault Relay (GFR). Bay 150 kV Srondol - Krapyak is the conductor that will be calculated proteksinya settings The analysis results show that in the high-voltage air channel GI 150 kV Srondol Rele distance as the main safeguard that protects high-voltage air channel Srondol - krapyak with setting (zones and time) with Z1 = 1.764853120 Ω with T1 = 0 s (instant), Z2 = 2.578424893 Ω with T2 = 0.4 s and Z3 = 4,905991928 Ω with T3 = 1.6 s. Overcurrent relay and ground disturbance as reserve safeguard protecting high-voltage air duct Srondol - Krapyak with setting Over current Rele = TMS 0.48 with working time of 1 s, ground noise Rele = TMS 0.63 with 1 s working time. Coordinate the time between the releases of distance as the main safeguard and overcurrent relay, the soil disturbance release as a backup safeguard is appropriate.